BEYOND BIG BIRD: THE ROLE OF HUMOR IN THE AGGREGATE INTERPRETATION OF LIVE-TWEETED EVENTS - Driscoll, Kevin; Leavitt, Alex; Guth, Kristen; Bar François (AoIR Selected Papers of Internet Research, 2015)
How do emergent discourses impact the interpretation of large social media events? A wide body of literature and prototypes in both academia and industry has attempted to aggregate and summarize valences, sentiment, and other linguistic and contextual factors from social media data, though few have taken into account the wide-ranging emergent behaviors of individuals and groups. Debates about the value of measuring opinion through this medium have challenged the interpretation of such techniques to summarize a vast array of contributions (Sifry, 2012; Metaxas et al., 2011; Gayo-Avello, 2011). This paper contributes to this debate through a multi-faceted analysis of tweets posted during each of the three 2012 presidential debates. Some studies have documented the practice of live-tweeting during televised media events (Bruns & Burgess, 2011; McPherson et al., 2012; Shamma, Kennedy, & Churchill, 2010; Schirra, Sun, & Bentley 2014). We focus on retweeting and livetweeting practices, in particular as they relate to humor, as we suspect prevalent sentiment analysis approaches may overemphasize their importance in political discourse. We examine practices such as the use of humor and sarcasm (Mejova, Srinivasan, & Boynton, 2013), building from and extending our prior work in this area (AoIR 12).